Gamma-ray Laser: Some Notes - Gupta, Gagan (SCHOOL SCIENCE, 2015)
During the last six decades, since their invention, lasers have become common-place in our society. These devices, producing highly directional light of a single wavelength, are important on their own and also as critical components of various systems. These energetic devices have applications in almost all fields of research and applications ranging from tailoring clothes to music to cookery to medicines and surgery to defence or even to cooling and trapping neutral atoms (Metcalf and Straten, 2007). Lasers made up of different materials can be as small as two microns and as large as a football field (the free electron laser - FEL). Their development has been characterised by a successive series of shorter-wavelength-lasers. The development of free-electron laser, first proposed by Madey in 1971, has significantly reduced laser wavelengths to sub-angstrom ranges. At the present state-of-the-art, lasers can emit radiations from infrared to hard X-ray regions. At the shortest wavelength, using an 8 GeV electron beam, scientists at SLAC (Stanford Linear Accelerator Centre) National Accelerator Laboratory at Stanford University have demonstrated the successful generation of laser light at 0.0634 nm, that is 63.4 pm (Emma, 2010) in a compact X-FEL device. The radiations produced are of wavelength four orders of magnitude smaller than the 694 nm produced by the first laser developed by Maiman in 1960.